First clinical realization of continuous monitoring of liver microcirculation after transplantation by thermodiffusion - Klar, Ernst; Kraus, Thomas W.; Bredt, Monika; Osswald, Brigitte; Senninger, Norbert; Herfarth, Christian; Otto, Gerd (Transplant international, 1996)
To date, no method is available for the continuous longterm monitoring of liver microcirculation in patients. Experimentally, thermodiffusion has been validated in the quantification of hepatic perfusion. In an attempt to investigate the practicability of thermodiffusion technology in patients after liver transplantation thermodiffusion probes were inserted into the graft in seven patients during liver transplantation. Continous monitoring started intraoperatively and was performed until day 7, when the probes were extracted transcutaneously. No probe-related complications (i. e., hemorrhage, infection) were observed. In four patients with normal graft function, liver perfusion recovered within 12 h from the intraoperative reduction to a range between 85 and 93 ml/100 g per min. In contrast, primary graft failure (n = 1) was characterized by a constant decrease of hepatic perfusion (< 50 m1/100 g per min). In prolonged reperfusion injury (n = 1), a second peak of transaminases was paralled by an impairment of liver microcirculation. In one patient, R2 rejection on day 7 was preceded by a drop in hepatic perfusion 48 h earlier. Thus, thermodiffusion is a safe and reliable method for the continuous quantification of liver microcirculation after transplantation in patients. Measurements are reproducible for at least 7 days. Changes in hepatic perfusion during postoperative complications can be detected. The characteristics of microcirculatory disorders will have to be defined in a larger number of patients.